Peran Genre Narkotika Di SMA Negeri 1 Kualuh Selatan Dalam Pencegahan Pemberantasan Penyalahgunaan Dan Peredaran Gelap Narkotika (P4GN) Di Labuhanbatu Utara - Indra Kumalasari M. (Universitas Islam Sumatera Utara, 2020)
The findings about the students who use narcotics are originated from trial and error. It is very influential on the behavior of the students themselves. This happens due to the inactivity of the role of narcotics genre in the implementation of the prevention program to eradicate abuse and illicit drug trafficking in North Labuhanbatu Regency. The purpose of this study was to determine the role of the narcotics genre that had been formed at SMA Negeri 1 South Kualuh in order to prevent illicit drug trafficking among students. The results of this study showed that the students of SMAN 1 South Kualuh has established the Narcotics Genre as an effort in the prevention of illicit trafficking of narcotics as well as the mandate of law No. 35 of 2009 on narcotics. However, the narcotics genre that has been formed has not been as effective as its role because it is only active at the provincial level competition for the role of narcotics genre. Knowledge about the danger of narcotics that have legal sanctions for the dealers and users is still not good in mastering the basic material. It is expected that the school will provide better material knowledge about the danger of narcotics and the school is more active in involving academics in this case those who have the main role include law enforcement, local government or North Labuhanbatu BNNK. Moreover, it is suggested for the local governments to be more active and to support the Narcotics Genre which already exists as well as at SMA Negeri 1 South Kualuh in North Labuhanbatu. Keywords: Narcotics GenRe Role in Prevention and Eradication